Versatile thiopyridyl/pyridinone porphyrins combined with potassium iodide and thiopyridinium/methoxypyridinium porphyrins on E. coli photoinactivation. (October 2020) - Calmeiro, Joana M.D.; Gamelas, Sara R.D.; Gomes, Ana T.P.C.; Faustino, Maria A.F.; Neves, Maria G.P.M.S.; Almeida, Adelaide; Tomé, João P.C.; Lourenço, Leandro M.O.
Abstract: Porphyrins (Pors) are well-known photoactive molecules with recognized features to be explored as photosensitisers in the photodynamic inactivation (PDI) of microorganisms. The use of appropriate moieties like pyridinium groups is a remarkable strategy to add peripheral and internal positive charges in the Por structure making them more effective PSs against Gram-negative bacteria like Escherichia coli ( E. coli ). In this context, an easy synthetic access to obtain cationic Zn(II) porphyrins bearing thiopyridinium and inverted methoxypyridinium units (ZnPors 1c and 2c ) was developed and their photo-physical and photo-chemical properties were evaluated. The photodynamic effectiveness of these complexes against a E. coli strain was also studied and compared with the efficacy of the corresponding free-bases (Pors 1b and 2b ) and of the neutral precursors (Pors 1, 1a, 2, 2a ), these last ones in the absence and in the presence of potassium iodide salt (KI). The obtained results demonstrate high PDI efficiency with the cationic free-base 1b and the ZnPor 2c ; both derivatives were able to photoinactivate E. coli till the detection limit of the method at a concentration of 1.0 μM after 20 and 15 min of white light irradiation (25 mW cm −2 ), respectively. Interestingly, under the same experimental conditions (1.0 μM and white light), the neutral Pors (1, 1a, 2 and 2a ) with addition of KI salt show a fast inactivation rate, reaching the detection limit of the method after 5 min of irradiation. Graphical abstract: Image 1 Highlights: PDI with neutral porphyrins combined with potassium iodide and cationic porphyrins were effective to photoinactivate E. coli. Neutral and cationic porphyrins are able to generate singlet oxygen under white light irradiation. Neutral porphyrins 1, 1a, 2 and 2a with addition of KI salt show a fast inactivation rate of the Gram-negative bacterium. Cationic PSs 1b, 1c, 2b and 2c (5 μM) promoted a decrease in the viability of E. coli till the detection limit of the method.